2007
DOI: 10.1111/j.1365-2702.2006.01593.x
|View full text |Cite
|
Sign up to set email alerts
|

The prevalence of enduring postnatal perineal morbidity and its relationship to type of birth and birth risk factors

Abstract: These findings highlight the need for further research and provide a number of challenges for health-care services and health-care professionals.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
33
1
2

Year Published

2013
2013
2021
2021

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 60 publications
(41 citation statements)
references
References 25 publications
(63 reference statements)
5
33
1
2
Order By: Relevance
“…Chein, Tai [42] found that at least one of the 18 physical symptoms surveyed was reported by 97.6% of women at one month and 91.6% at one year after delivery. Again, this finding is consistent with previous reports of a high prevalance of physical morbidity in women after childbirth [43][44][45] . Williams, Herron-Marx & Knibb [45] reported that 87% of women complained of at least one index of morbidity at 12 months postpartum.…”
Section: Physical Factors Associated With Perinatal Healthsupporting
confidence: 83%
See 1 more Smart Citation
“…Chein, Tai [42] found that at least one of the 18 physical symptoms surveyed was reported by 97.6% of women at one month and 91.6% at one year after delivery. Again, this finding is consistent with previous reports of a high prevalance of physical morbidity in women after childbirth [43][44][45] . Williams, Herron-Marx & Knibb [45] reported that 87% of women complained of at least one index of morbidity at 12 months postpartum.…”
Section: Physical Factors Associated With Perinatal Healthsupporting
confidence: 83%
“…Again, this finding is consistent with previous reports of a high prevalance of physical morbidity in women after childbirth [43][44][45] . Williams, Herron-Marx & Knibb [45] reported that 87% of women complained of at least one index of morbidity at 12 months postpartum. While Australian mortality rates are often distingished as the main indicator of a quality maternity service, there is emerging literature that suggests that these less severe health problems are highly prevelant and just as meaningful to childbearing women [46,47] .…”
Section: Physical Factors Associated With Perinatal Healthsupporting
confidence: 83%
“…Several studies noted that many women (up to 25%) with postpartum health problems did not consult a health professional [2,11].…”
Section: Discussionmentioning
confidence: 99%
“…Although surgery can correct pelvic organ prolapse, the surgery can also increase the risk of UI (Brown et al, 2000). Larger birth weight babies, multiple deliveries and the use of instrument assisted birth methods can cause major trauma to the pelvic floor therefore reducing perianal floor strength increasing the risk of UI (Friedman and Stothers, 2011, Hayman, 2005, Williams, Herron-Marx and Knibb, 2007and Thomas et al, 2007. It is also unclear whether cesarean delivery can help to prevent or reduce the risk of UI, as the weight of the baby and hormonal changes may have already lead to UI (Sangsawang, 2014).…”
Section: Risk Factors Pregnancy and Childbirthmentioning
confidence: 99%